A STUDY ON THE WRITING ENGLISH BUSINESS LETTER DIFFICULTIES AT THE FIRST YEAR STUDENTS ACCOUNTING DEPARTMENT OF SMKN 1 BANDAR SEIKIJANG - Dahler Dahler (Universitas Lancang Kuning, 2017)
Students at the first year students accounting department of SMKN 1 Bandar Seikijang had problems in writing English business letter. They were facing difficulties type of English business letter. The Purpose of this research was to find out what kind of difficulties in writing the English business letter faced by the first year students accounting department of SMKN 1 Bandar Seikijang. The design of this research was survey. Sample of the research was 23 students at the first year students accounting department of SMKN 1 Bandar Seikijang. Instrument used was questionnaire. The questionnaire was about the students' difficulties in writing the English business letter. The questionnaire was analyzed by using percentage formulation. The result of analyzing data that the students' response toward their difficulties in writing the English business letter was making up negative response with 71.73%.In conclusion, the students at the first year students accounting department of SMKN 1 Bandar Seikijang had trouble in studying style of letter in English business letter. Keyword : Business Letter Writing, Difficulties